Die Lebenszeugnisse Oswalds von Wolkenstein - Oswald,Schwob, Anton (Böhlau, 2004)
The historical source materials edited in the 3rd volume, which were collected in more than 40 archives and libraries in Austria, Italy, Germany, Czechia and Switzerland, present Oswald von Wolkenstein as a legal expert, warrior, diplomat, princely servant as well as unrestless politician. He is at feuds with opponents in matters of legacy and engages in the Vehmic courts as a juryman, but is also a versatile servant of the King, princely counsellor and tenacious judge. Through his important role in the local judicature, he achieves high reputation in Tyrol. Das im 3. Band edierte Quellenmaterial aus Archiven und Bibliotheken Österreichs, Italiens, Deutschlands, Tschechiens und der Schweiz präsentiert Oswald von Wolkenstein als Rechtssachverständigen, Krieger, Diplomaten, Fürstendiener und unermüdlichen Politiker. Er führt Fehden und betätigt sich als Freischöffe der Feme, aber auch als wendiger Diener des Königs, umsichtiger Fürstenberater und zäher Prozessführer. In Tirol gelangt er durch seine bedeutende Rolle im heimischen Rechtsleben zu hohem Ansehen.
Literaturverz. S. 327 - 350